Anaerobic and aerobic contributions to 800 m and 8 km season bests - Blumkaitis, J. C.; Sandefur, C. L.; Fahs, C. A.; Rossow, L. M. (Journal of Trainology, 2016)
Objective: Both anaerobic and aerobic factors contribute to distance running performance. How these factors relate to middle and long distance running performance in National Association of Intercollegiate Athletics (NAIA) runners has not been previously determined. The purpose of this study was to examine relationships between anaerobic and aerobic assessments and two season best race times (800 m and 8 km) in NAIA runners participating in track and cross-country at a small Midwestern American college. Design: This study employed a cross-sectional design. Data was collected from a lab visit as well as from season best running times. Methods: 11 subjects (f = 4) completed a graded exercise test for VO2max and ventilatory threshold assessment, a 40 m sprint, a standing long jump, and a vertical jump. Correlations were performed between 800 m and 8 km season bests and the afore mentioned tests. Results: 800 m run time correlated only with VO2max (r = -.600; p = .044). 8 km run time correlated most strongly with vertical jump height (r = -.823; p = .011) but also with 40 m sprint (r = .704; p = .039) and VO2max (r = -.670; p = .047). Conclusions: Anaerobic and aerobic contributions to season best race times in NAIA runners were slightly different than expected based on previous work in different populations. This information may be useful for NAIA track and cross-country coaches interested in determining tests that best relate to running performance in their athletes.